Creating the magical world. - Khairunnisa Abdul Rashid. (2011)
A creative writing piece based on a boy who gets lost in a Carnival. He soon learns that he has magical abilities which the owners of the Carnival are yearning to get their hands on. Together with a group of friends, he plans to escape the Carnival and return back home to his parents.